A cross-sectional survey on the patterns of primary teeth eruption in 2 581 children - Li, R X (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2017)
Objective: To investigate the patterns of primary teeth eruption by a cross-sectional survey in 0-40 months old children in Chongqing and to provide normal timetables of tooth eruption that are practical in general physical growth assessment. Method: Data of 2 581 0-40 months old healthy children were collected from January 2014 to January 2016 at Children's Hospital of Chongqing Medical University. General information was recorded by primary child health care doctors, including age, gender, gestation age, birth weight, time and sequence of first primary tooth eruption, number of teeth and age of totally primary teeth emergence. Median and constituent ratio were used in describing the age of tooth eruption and eruption characteristics at different age. Moreover, independent-sample t test, variance analysis, Pearson product-moment correlation and Logistic regression were also involved in data analysis. Result: Totally 2 581 children were involved in this survey, including 506 infants of 0-6 months old, 600 infants of 7-12 months old, 730 toddlers of 13-24 months old and 745 children of 25-40 months old. There were 1 473 boys and 1 108 girls, 89 preterm babies and 2 492 full term babies, 1 829 children with tooth erupted and 626 children with all primary teeth erupted.The age of the first primary tooth eruption was between 2-15 months old ( median age: 8 months old, 95%CI: 2.7-12.7)and for the last primary tooth emergence was between 23-35 months of age (median age: 31 months, 95%CI: 24.7-36.7). The time of first tooth eruption was positively correlated with that of total teeth emergence (r=0.879, P<0.05). Dental charts (number of tooth for age) of different gender were drawn according to teeth eruption information. The first primary tooth eruption was the incisor of mandible in 95.3% (1 743/1 829)infants and was the incisor of maxilla in 4.6% (84/1 829)infants. During the period of tooth emerging actively (number of teeth ≤16), the number of primary teeth might be calculated by formula: number of teeth=chronological age in months-age of first eruption in months+ 1. There was no statistically significant difference between the number of actual teeth and calculated by the present formula(t=-2.957, P=0.05). Conclusion: The median age of first primary tooth eruption and total teeth emergence was 8 and 31 months of age respectively. The first primary tooth eruption is incisor of mandible in most infants.The formula (number of teeth=chronological age in months-age of first eruption in months+ 1 )can be used to estimate the number of primary teeth. Dental charts might provide normal and supplement datasets for evaluating child physical growth